Intensive linear and nonlinear optical studies of thermally evaporated amorphous thin Cu-Ge-Se-Te films - Hassanien, Ahmed Saeed (Journal of non-crystalline solids, 2022)
•Novel a-Cu-Ge-Se-Te (0 ≤ x ≤ 20 at.%) thermally evaporated thin films were prepared.•Optical constants and other parameters were studied using T, R, and A-spectra.•Dispersion energy and parameters were deduced using WDD and Sellmeier postulate.•Dielectric constants, energy loss functions and non-linear parameters were studied.•The studied dielectric and optoelectronic parameters depend strongly upon the photon wavelength and Cu-content. This article is devoted to completing the study of linear and nonlinear optical characteristics of thermally evaporated a-CuxGe20-xSe40Te40, CGST, (0 ≤ x ≤ 20 at.%) thin films. The film thickness and rate of deposition were fixed in 2000 Å and 100 Å/s, respectively. Optical constants of CGST-films have been deduced from spectrophotometric measurements in the spectral range 300nm-2500 nm. The VB and CB potentials have been determined; their values increase from 0.344 eV to 0.404 eV for the CB, while increases from (-0.864 eV) to (-0.641 eV) for VB, as Cu-percentage increases. Wemple-DiDomenico single oscillator model is applied to obtain dispersion energies and parameters. The single oscillator energy decreases from 2.411 eV to 2.232 eV, while the dispersion energy increases from 14.974 eV to 20.763 eV, as Cu-ration increases. Many other important optoelectrical and dielectric parameters have also been discussed, like static refractive index, average oscillator wavelength, oscillator-length strength parameters. The surface and volume energy loss functions, optical complex conductivity (real and imaginary parts), electronic polarizability, and some nonlinear optical parameters are also well-discussed. Total electronic polarizability values increase from 4.560 Å to 3.088 Å, while the plasma frequency increases from 4.200×1014 Hz to 3.970×1014 Hz. All mapped parameters have been discussed and linked to each other, as well as studying their dependence on Cu-ratio.